(untitled) (West African Journal on Sustainable Development, 2024)
Urbanization is rapidly expanding across the globe, leading to increasing threats to wildlife in and around cities. As urbanization continues to expand, it is crucial to find ways to create cities that are not only livable for humans but also supportive of animal and wildlife populations. By incorporating thoughtful design, conservation efforts, and community engagement, cities can become havens for biodiversity, promoting coexistence and enhancing the overall well-being of both humans and animals. We review several strategies to transform cities into animal and wildlife-friendly environments. These include Encourage the use of native plants in urban landscaping, Protecting existing green spaces like parks and gardens, Design and implement wildlife corridors that connect different natural areas within the city, Implement bird-friendly building standards to reduce hicollisions with glass windows, Design infrastructure with animal-friendly features in mind. Educate residents about the importance of wildlife Conservation and the role they can play in creating animal-friendly cities. Collaborate with various stakeholders, such as local governments, businesses, NGOs, and community groups, to develop and implement animal and wildlife-friendly policies, Develop and enforce responsible waste management practices to reduce the attraction of wildlife to urban areas, Promote community gardens and allotments to provide additional green spaces and food sources for wildlife and work with local Conservation organizations to establish wildlife conservation programs such as habitat restoration projects.